Effects of Moringa oleifera in Two Independents Formulation and as Neuroprotective Agent Against Scopolamine-Induced Memory Impairment in Mice - Arozal, Wawaimuli; Purwoningsih, Emni; Lee, Hee Jae; Barinda, Agian Jeffilano; Munim, Abdul (Frontiers in Nutrition, 2022)
Background The cognitive deficit has frequently been found in the elderly population. Several studies have shown that every single part of Moringa oleifera, including leaves, roots, and seeds, has abundant micronutrients, such as flavonoids, which improve the neurobehavioral capacity. However, herb parts that display optimal neuropharmacological properties remain unknown. Objective We investigate whether M. oleifera seed oil (MOO) or aqueous M. oleifera leaves extracts (MOEs) may ameliorate memory impairment in mice induced with scopolamine (Sco). Additionally, the phytochemical analyses of those two independent formulations were analyzed. Methods In this study, 2 ml/kg body weight (BW) of MOO and 500 mg/kg BW of MOE were orally administered to the mice for 28 days, followed by intraperitoneal injection of Sco (1 mg/kg) at the day 22–28 to induce cognitive impairment in those mice. Results The Sco group showed memory retention impairment represented by the Y-maze and novel object recognition tests, significant enhancement of acetylcholine esterase (AChE) activity in hippocampus tissue (p < 0.0001), and increased the level of total antioxidant capacity (TAOC) in serum. Interestingly, the Sco-induced memory defect was improved and completely blunted the AChE exacerbation in Sco+MOO-treated mice (p < 0.0001), although the TAOC level was comparable among the groups. Mechanistically, both tropomyosin receptor kinase B (TrkB), as a brain-derived neurotrophic factor-receptor, and nuclear factor-kappa-light-chain-enhancer of activated B cells (NF-κB) protein expressions were enhanced with the hippocampus isolated from the Sco group. Nonetheless, pretreatment with MOO only, but not with MOE, ameliorated the enhanced protein expression levels of TrkB and NF-κB (p < 0.05 and p = 0.09, respectively). Conclusion Our data reveal that MOO is preferable to MOE as a neuroprotective as evidenced by improving memory impairment. This effect, at least in part, through inhibiting the AChE and NF-κB activities and modulating the TrkB expression level.